ANÁLISIS DE LA GLOBALIZACIÓN EN EL DERECHO ADMINISTRATIVO (2019)
This article is the result of an investigation through the analysis and synthesis of the doctrine and specialized jurisprudence on comparative administrative law method, and its impact on legal globalization, in relation to international standards of administrative justice. The central hypothesis is that, regarding administrative justice, there is an adaptation to international standards, which makes it necessary to accommodate the national regulations to doctrine and international jurisprudence tendencies, which leads to the recognition of a wide possibility of immersion of the rules of administrative law, and in general of all public law, towards compliance with international standards of public administration rules.